Corneal Aberrations, Contrast Sensitivity, and Light Distortion in Orthokeratology Patients: 1-Year Results - Elena Santolaria-Sanz; Alejandro Cerviño; José. M. González-Méijome (Journal of Ophthalmology)
Purpose. To evaluate the corneal higher-order aberrations (HOA), contrast sensitivity function (CSF), and light distortion (LD) in patients undergoing orthokeratology (OK). Methods. Twenty healthy subjects (mean age: 21.40±8 years) with mean spherical equivalent refractive error M=-2.19±0.97 D were evaluated at 1 day, 1 month, and 1 year after starting OK treatment. Monocular LD, photopic monocular CSF, and corneal HOA for 6 mm pupil size were measured. Results. LD showed an increase after the first night (p<0.05) and recovery to baseline after 1 month, remaining stable after 1 year (p>0.05). Spherical-like, coma-like, and secondary astigmatism HOA RMS increased significantly (p≤0.022) from baseline to 1-month visit, remaining unchanged over the follow-up. Contrast sensitivity for medium frequencies (3.0, 4.24, and 6.00 cpd) was significantly correlated with LD parameters at baseline (r≤-0.529, p<0.001). However, after 1 year of treatment, this correlation was only statistically significant for 12 cpd spatial frequency (r≤-0.565, p<0.001). Spherical-like RMS for 6 mm pupil size correlated with irregularity of the LD (r=-0.420, p<0.05) at the 1-year visit. Conclusion. LD experienced by OK patients recovers after one month of treatment and remains stable in the long term while optical aberrations remain significantly higher than baseline.